Innovation Promoter or Inhibitor? Non-Family CEO's Effect on Innovation in Family Businesses - Chung, Pi-Hui; Lee, Chia-Jung; Wu, Hsueh-Liang; Lee, Cheng-Yu (IEEE transactions on engineering management, 2023)
Increasing scholarly and practical attention is being paid to determining whether a nonfamily chief executive officer (NFC) is a remedy for the lack of firm innovativeness in the face of ever-changing markets. Departing from the inconclusive findings of NFC research, this article aims to revisit the NFC effect on a family firm's investment in innovation, which is subject to the contextual influence of governance arrangements. In a sample of 6201 firm-year observations of Taiwanese family firms in high-tech industries in the period from 2002 to 2017, we found that the mixed relationship between the NFC and innovation investment is better clarified by considering family involvement in management (FIM) and board independence (BI), both of which yield significantly negative and positive moderating effects on the innovation investment of NFCs, respectively. This article further examines the configurational effect of two moderators on the main relationship, and shows that the negative effect of FIM not only outweighs, but also deteriorates, the positive moderating effect of BI. Our findings contribute not only to family business research, but also to innovation literature by arguing that the risk-taking orientation of an NFC is not universally held, but rather is deliberately arranged for effect.